2016
DOI: 10.1093/ofid/ofw092
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Human Immunodeficiency Virus-Associated Hypergammaglobulinemia Reduces Transplacental Transfer of Immunoglobulin G to Plasmodium falciparum Antigens in Cameroonian Neonates

Abstract: Background. Human immunodeficiency virus (HIV) infection reduces placental transfer of antibodies from mother to the fetus for many antigens; however, conflicting data exist for transfer of immunoglobulin G (IgG) to malarial antigens. The mechanism(s) underlying reduced placental transfer is unknown.Methods. Levels of maternal and cord total IgG, IgG subclasses, and cord-to-mother ratios (CMRs) were measured in 107 mother-cord pairs to 3 malarial antigens: circumsporozoite protein (CSP), apical membrane antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 45 publications
4
28
1
Order By: Relevance
“…In contrast, Moro et al found that HIV+ Mozambican women (receiving no ART) had reduced CMR of antibodies against MSP1, Pf lysate, AMA1, and EBA175 [26]. HIV+ Cameroonian women who received only nevirapine at delivery had decreased CMRs to CSP, AMA1, MSP1, and tetanus compared with HIV- women [47]. This was thought to be driven by elevated hypergammaglobulinemia in HIV+ women, but after adjusting for this, decreased CMR of CSP, MSP1, and tetanus persisted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Moro et al found that HIV+ Mozambican women (receiving no ART) had reduced CMR of antibodies against MSP1, Pf lysate, AMA1, and EBA175 [26]. HIV+ Cameroonian women who received only nevirapine at delivery had decreased CMRs to CSP, AMA1, MSP1, and tetanus compared with HIV- women [47]. This was thought to be driven by elevated hypergammaglobulinemia in HIV+ women, but after adjusting for this, decreased CMR of CSP, MSP1, and tetanus persisted.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that we did not measure IgG subclasses to vaccine or Pf antigens, which might have increased our ability to detect differences in CMRs according to maternal HIV or malaria infection, as observed in some studies that detected significant differences in antimalarial IgG1 and IgG3 CMRs but not in total antimalarial IgG [26, 47]. Additionally, baseline differences between HIV+ and HIV- women (most notably age and gravidity) affect their risk for malaria during pregnancy in that younger and primi- or secundi-gravidae women are at highest risk [50].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IgG Ab levels to VAR2CSA recombinant proteins (FV2 and DBL5) of the FCR3 strain, expressed in Baculovirus-transfected insect cells, were measured using a multi-analyte platform (MAP). The coupling of the recombinant proteins to MagPix microspheres and basic protocol have been described previously [21,24,25]. Briefly, 50 μl of antigen-coupled microspheres (2000 microspheres/antigen) were incubated in a well of a microtiter plate (U-bottom microplate) with 50 μl of plasma diluted to 1:100 in phosphate buffered saline containing 1% bovine serum albumin (PBS 1% BSA) for 1 h at room temperature on a rotating shaker at 500 rpm (Microplate Shaker, Lab-line, Melrose Park, IL, USA).…”
Section: Measurement Of Antibodiesmentioning
confidence: 99%
“…The effect of maternal HIV infection is also controversial. Some studies demonstrated that HIV infection leads to a reduction of the transplacental transfer of Hib , diphtheria, pertussis, pneumococcus, measles, tetanus, and Plasmodium falciparum ( P. falciparum ) specific antibodies ( 28 , 29 , 39 45 ), but others have shown no effect ( 29 , 33 , 38 , 41 , 42 , 46 ). Those studies had several limitations, as the numbers of antigens tested and HIV-infected women included in the analyses were low.…”
Section: Introductionmentioning
confidence: 99%